APPLICATION OF GUIDED INQUIRY LEARNING MODEL ON MATHEMATICAL PROBLEM SOLVING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS N 1 BASO - Melia Roza; Fepryna Yenti; Majidah Khairani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
The research aims to determine whether students' mathematical problem-solving skills using the guided inquiry learning model are better than students with conventional learning in seventh grade students at SMPN 1 Baso. This type of research is a quasi-experimental with a randomized control group only design. The research population was seventh grade students at SMPN 1 Baso which were divided into seven classes with 138 students. The sample in this study were 20 students in class VII1 as an experimental class and 20 students in class VII2 as a control class taken through simple random sampling. The research instrument was the final test in the form of essay questions related to mathematical problem solving abilities. The results of the final test will be used to test the hypothesis with the t-test with a = 0.05 and dk = 36. The analysis shows that the average problem-solving ability score in the experimental class is higher when compared to the control class. Based on the t test, it was found that students' mathematical problem solving abilities with inquiry learning models were better than students with conventional learning models.